Penetapan Kadar Kafein Dari Ekstrak Daun Kopi Robusta (Coffea canephora Pierre ex A. Froehner) Dan Daun Kopi Arabika (Coffea arabica L.) Dengan Metode Kromatografi Cair Kinerja Tinggi. - Tri Damaiyanti; Muhammad Amin Nasution; Haris Munandar Nasution; Rafita Yuniarti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Coffee is a plant that contains caffeine and can be processed into a delicious drink. Currently, it has achieved very high popularity throughout the world, ranking second after water and tea in the list of most preferred drinks. Coffee drinks are popular with various groups, from teenagers to adults, and in Indonesia, coffee is even the most giant drink consumed, only behind water in consumption levels. On average, people consume coffee around 3-4 times a day, reflecting how popular this drink is among the Indonesian population. Coffee has relatively high levels of caffeine, and continued excessive consumption can increase the risk of developing several types of diseases, such as hypertension, heart disease, and stroke. According to the Food and Drug Monitoring Agency (BPOM), the maximum limit for caffeine consumption in food and drinks is 150 mg per day and 50 mg per serving. Excessive and continuous coffee consumption can increase the risk of developing certain diseases such as hypertension, heart disease and stroke. This research aimed to determine the secondary metabolite content of robusta coffee leaves and arabica coffee leaves and to determine the caffeine content in robusta coffee leaves and arabica coffee leaves using high-performance liquid chromatography. The stages of this research include processing plant material, characterisation, making ethanol extract, phytochemical screening, and determining caffeine content in robusta coffee leaf extract and Arabica coffee leaves using high-performance liquid chromatography. Extracts from Robusta coffee leaves and Arabica coffee leaves are made using the maceration method using 96% ethanol. The resulting extract was then concentrated using a rotary evaporator, and qualitative testing of caffeine was carried out using the Parry method. Caffeine levels were determined using high-performance liquid chromatography, using the regression equation y = ax+b, where y is the area, a= 49.668, and b= - 16.536. The caffeine content in Robusta coffee leaf extract was measured at around 51.42916 mg/g, while Arabica coffee leaf extract had a caffeine content of around 29.97927 mg/g.